Genetic analysis of salt tolerance at seedling and reproductive stages in rice (Oryza sativa) - Mohammadi, Reza; Mendioro, Merlyn S.; Diaz, Genaleen Q.; Gregorio, Glenn B.; Singh, Rakesh K. (Wiley, 2014)
Salinity is a major abiotic stress that limits rice production across rice areas as high‐yielding modern rice varieties are generally sensitive to salt stress. The study was conducted to deduce heritability and combining ability estimates of rice for various morphological and physiological traits using a 7 × 7 full‐diallel‐cross analysis at seedling and reproductive stages. The salinity stress treatment was 12 dS m−1 at the seedling stage and 8 dS m−1 at the reproductive stage. Diallel analysis revealed high for salinity tolerance scores and shoot height, moderate for shoot dry weight and root dry weight and low for Na+ and K+ concentrations and K+/Na+ ratio. The low‐to‐moderate narrow‐sense heritability for number of panicles, number of fertile spikelets, grain weight, spikelet fertility and K+/Na+ ratio suggests a large breeding population and delayed selection for tolerance until later generations. Significant maternal effects indicate that selection of the female parent is very important for desired trait development. The results of this study confirmed that salinity tolerance at the seedling and reproductive stages is regulated by a different set of genes that could be pyramided using different donors to enhance the level of tolerance.